A local pointwise inequality for a biharmonic equation with negative exponents. (1st January 2023) - Chen, Fan; Chen, Jianqing; Ruan, Qihua
Abstract: In this paper, we are inspired by Ngô, Nguyen and Phan's (2018 Nonlinearity 31 5484–99) study of the pointwise inequality for positive C 4 -solutions of biharmonic equations with negative exponent by using the growth condition of solutions. They propose an open question of whether the growth condition is necessary to obtain the pointwise inequality. We give a positive answer to this open question. We establish the following local pointwise inequality − Δ u u + α | ∇ u | 2 u 2 + β u − q + 1 2 ⩽ C R 2 for positive C 4 -solutions of the biharmonic equations with negative exponent − Δ 2 u = u − q i n B R where B R denotes the ball centered at x 0 with radius R, n ⩾ 3, q > 1, and some constants α ⩾ 0, β ⩾ 0, C > 0.